Mid-term outcomes in the treatment of retroperitoneal sarcomas: a 12-year single-institution experience - Georgios-Ioannis Verras; Francesk Mulita; Konstantinos Bouchagier; Dimitrios Bousis; Dimitrios Kehagias; Elias Liolis; Ioannis Perdikaris; Dimitrios Filis; Panagiotis Perdikaris; Ioannis Panagiotopoulos; Ioannis Maroulis; Nikolaos Benetatos (Medicinski glasnik, 2022)
Aim: To present the experience from collective data regarding patients with retroperitoneal sarcomas that have been operated in and followed up by the University General Hospital of Patras in Rion, Greece, between 2009 and 2020. Methods: A retrospective analysis of adult patients treated at our hospital with a diagnosis of primary retroperitoneal sarcoma who underwent tumour resection. Results: Data from 29 patients were analysed. The mean age at diagnosis was 56.1 years; 55.2% of patients were male (n=16). Liposarcomas (on histology) were identified in 19 (65.5%) patients, leiomyosarcoma six (20.7%), and other histologic subtypes in four (13.8%) patients. Tumours >5cm were presented in 27 (93.1%) patients. Negative margins were attained in 13 (44.8%) of all patients who underwent surgical resection. Five (17.2%) patients received neoadjuvant radiation, four (13.8%) postoperative radiation, and three (10.3%) patients received both chemotherapy and radiation prior to surgery with the rest of the patients being treated with surgical excision alone. A 3-year follow-up was successful in 21 (72.4%) patients; five (23.8%) patients died. In total, 16 (55.2%) patients were found to have a local recurrence, with no significant difference in patients' age, gender, tumour size, histology, negative surgical margin (Ro) resection, neoadjuvant chemotherapy, or radiation therapy. There was a significant difference in the 3-year survival rate between patients having positive or negative surgical margins (p=0.027). Conclusion: The higher 3-year survival rate in patients with retroperitoneal sarcomas when achieving Ro resection warrant further investigation with a larger sample size across different institutions.
Keywords: liposarcoma; negative surgical margins; radiotherapy; survival